Increased risk of hip fracture associated with dually treated HIV/hepatitis B virus coinfection. Issue 11 (6th March 2015) - Byrne, D. D.; Newcomb, C. W.; Carbonari, D. M.; Nezamzadeh, M. S.; Leidl, K. B. F.; Herlim, M.; Yang, Y. X.; Hennessy, S.; Kostman, J. R.; Leonard, M. B.; Localio, A. R.; Lo Re, V.
Summary HIV and hepatitis B virus (HBV) infections are each associated with reduced bone mineral density, but it is unclear whether HIV/HBV coinfection is associated with an increased risk of fracture. We determined whether dually treated HIV/HBV patients had a higher incidence of hip fracture compared to treated HBV‐monoinfected, antiretroviral therapy (ART)‐treated HIV‐monoinfected and HIV/HBV‐uninfected patients. We conducted a cohort study among 4156 dually treated HIV/HBV‐coinfected, 2053 treated HBV‐monoinfected, 96 253 ART‐treated HIV‐monoinfected, and 746 794 randomly sampled uninfected persons within the US Medicaid populations of California, Florida, New York, Ohio and Pennsylvania (1999–2007). Coinfected patients were matched on propensity score to persons in each comparator cohort. Weighted survival models accounting for competing risks were used to estimate cumulative incidences and hazard ratios (HRs) with 95% confidence intervals (CIs) of incident hip fracture for dually treated coinfected patients compared to (i) HBV‐monoinfected receiving nucleos(t)ide analogue or interferon alfa therapy, (ii) HIV‐monoinfected on ART and (iii) uninfected persons. Dually treated coinfected patients had a higher cumulative incidence of hip fracture compared to ART‐treated HIV‐monoinfected (at 5 years: 1.70% vs 1.24%; adjusted HR, 1.37 [95% CI, 1.03–1.83]) and uninfected (at 5 years: 1.64% vs 1.22%; adjusted HR, 1.35 [95% CI, 1.03–1.84]) persons. The cumulative incidence of hip fracture was higher among coinfected than treated HBV‐monoinfected patients (at 5 years: 0.70% vs 0.27%), but this difference was not statistically significant in competing risk analysis (adjusted HR, 2.62 [95% CI, 0.92–7.51]). Among Medicaid enrollees, the risk of hip fracture was higher among dually treated HIV/HBV‐coinfected patients than ART‐treated HIV‐monoinfected and uninfected persons.